Restoration of Architectural Heritage - Kolisnychenko, Stanislav (Specialized collections, 2017)
The conventional and unconventional materials, modern engineering methods and technologies employed in the restoration and reconstruction of architectural heritage are the topics of the aggregated edition "Restoration of Architectural Heritage". The book contains the scientific articles selected from the materials published by Trans Tech Publications Inc. from 2010 to 2016 inclusive. We hope this collection will be useful for many readers whose activity refers to the architectural heritage preservation sphere. Architectural Heritage, Restoration, Reconstruction, Conversion, Construction Technology, Wood and Timber, Conventional Materials, Unconventional Materials, Rising Damp, Moisture, Seismic Assessment and Protection, Structural Analysis and Monitoring, Urban and Rural Planning.